Accession incentives for institutional change in post-socialist countries: cross-section and country evidence from NATO enlargement - Rainer Schweickert; Inna Melnykovska; Hanno Heitmann (Kiel Institute for the World Economy (IfW), 2010)
This paper analyses the transformative power of NATO accession that gains in importance due to the enlargement fatigue of the EU, the EU's rather weak neighbourhood incentives and the increasing importance of regional security as an incentive for compliance with the institutional standards of democracy and market economy. Econometric cross-country evidence from a hazard model reveals that the entry into NATO's accession process is mainly driven by neighbourhood and strategic effects rather than foregoing institutional reforms in a candidate-country. While strategic interests also dominated the accession process of Macedonia initially, the case study results reveal the central role of the switch in NATO's strategy from strategic interest only to a more balanced consideration of institutional reforms, which `turned Macedonia around' in terms of institutional development. Clearly, after this turning point marked by the Ohrid agreement, the effectiveness of NATO's accession conditionality could be revealed. The switch in NATO's strategy, rather enforced externally than the result of a well structured debate among NATO members, is of special relevance for the peaceful transition of other post-socialist countries, e.g. Ukraine and Georgia.
Keywords: F59; P30; O19; 330; NATO Enlargement; Democratization; Institutions; Transition; Conflict; FYR Macedonia